Online Food Delivery System Success Model: The Role of Brand Image in Customer Response - Priscilia, Meshanda; Sumar, Sumar (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Among all industry sectors, the food industry’s e-business volume grew at the fastest rate in 2020 (434%). The market for online food delivery is expected to increase at a rate of 6.36% per year between 2021 and 2024. For this reason, ordering food online via websites or applications has grown in importance within the distribution chain of restaurants. This study’s primary goals are to find out the relationship between system experience and brand image as well as the impact of brand image on customer satisfaction. The research theoretical framework is based on the Stimulus-Organism-Response (SOR) paradigm. The DeLone and McLean Information Systems Success Model is also used in this study. The total system quality (information, system, and service quality) serves as the “stimulus” in this context. Brand image as the “organism” and customer satisfaction serves as the “response”. The findings showed that the quality of information had no positive effect on customer satisfaction. Meanwhile, the quality of the system and service has a positive effect on the brand image. This research shows the importance of brand image in creating customer satisfaction in the online food delivery industry. The findings of this study contribute to companies that want to choose an online food delivery service provider.